International climate policy: Priorities of key negotiating parties - Susanne Dröge (Stiftung Wissenschaft und Politik (SWP), 2010)
International climate policy has received an unprecedented attention in 2009 and 2010. However, the Copenhagen summit of 194 members to the United Nations Framework Convention on Climate Change (UNFCCC) in December 2009 did not result in a new international binding treaty for climate protection, adaptation, technological cooperation or financial transfers. Instead, a political declaration, the Copenhagen Accord, was set up which includes a number of important cornerstones for a future regime. While the Accord declares that high financial transfers will be delivered by 2012, it lacks a clear path for reaching the two degrees target proclaimed as an overarching goal. Given the slow progress, efforts by Germany and the EU should more than ever focus on the national interests of major economies and emitters, in particular the US, China, India, and Russia, and on cooperating more closely with the proactive climate negotiators Brazil and South Africa.This Research Paper presents the climate policy priorities of the six countries and the EU. It departs from their self-perception in international negotiations and from the role climate policy plays for their foreign policy agenda. Besides being major international players, all countries target economic growth and this dominates the willingness to act against emissions - an argument playing out to the full in international negotiations. Thus, international efforts to combat climate change need a much broader political basis incorporating economic and development cooperation. Our research on the six countries and the EU delivers insights on particular bilateral and multilateral common interests, which would not only bring forward international cooperation on a future legal framework, but also and foremost effective action against rising emissions
Keywords: 320; Global